P5_9 Wolves, Deer, and a Python...Model - Sharman, Mark; Knott, George; Rayson, Ben; Molloy, David (Physics Special Topics, 2022)
In this paper, we present our Python model which determines the consequences of Grey Wolf reintroduction on Red Deer numbers in a small area of Scotland. The model is constructed using the Lotka-Volterra method and integrated via the Runge-Kutta method. We find that introducing a single pack of 10 wolves reduces the deer numbers and creates an oscillation in population with a period of $\sim$10 years.